2016
DOI: 10.1590/s0102-865020160040000002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peritoneal endometriosis treatment using intralesional acetylsalicylic acid injection in rabbits

Abstract: PURPOSE:To investigate the efficacy of intralesional 20% aspirin injection for treatment of experimental peritoneal endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A high level of COX-2 due to various factors such as estrogens, hypoxia and environmental pollutants could suppress apoptosis and increase cell proliferation through PGE2 and its receptors EP2, and EP4 in endometriosis (143). In addition, experimental studies with intralesional injections of ASA, in rabbits with peritoneal endometriosis, eliminate endometriotic lesions (144).…”
Section: Lipoxinsmentioning
confidence: 99%
“…A high level of COX-2 due to various factors such as estrogens, hypoxia and environmental pollutants could suppress apoptosis and increase cell proliferation through PGE2 and its receptors EP2, and EP4 in endometriosis (143). In addition, experimental studies with intralesional injections of ASA, in rabbits with peritoneal endometriosis, eliminate endometriotic lesions (144).…”
Section: Lipoxinsmentioning
confidence: 99%
“…22 In animal studies, intralesional aspirin injections caused destruction of peritoneal endometriosis. 23,24 Other studies have assessed the effects of herbal antioxidants. 25 Our study indicated that short-term administration of aspirin to women with endometriosis reduced chronic pelvic pain, dysmenorrhea, and dyspareunia in these women.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet depletion or suppression of platelet aggregation is an interesting approach and preclinical studies are running. Primary results with intralesional aspirin injection 44,45 or other antiplatelets are encouraging by effectively reducing lesion growth and the extent of fibrosis 46,50 .…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results of Saad-Hossne et al showed that intralesional aspirin injection resulted in elimination of gross and histological areas of endometriotic tissue, leaving only fibrosis, necrosis, and apoptosis in their place with a good safety profile. As the scar tissue can negatively impact on local tissue function and culminate in clinical manifestations, further investigations should examine the real scar tissue formation rate and its clinical implications, such as fertility, after intralesional aspirin injection 44 . Siquiera et al issued also encouraging results with intralesional injection with aspirin in endometriotic lesions in rabbits 45 .…”
Section: The Role Of Antithrombotic Treatment Antiplatelet Treatment and Platelet Depletionmentioning
confidence: 99%